ABO / Rh-D Blood types and susceptibility to SARS-CoV-2 infection in Health Care Workers - Rahim, Fawad; Amin, Said; Noor, Muhammad; Mahmood, Afsheen; Gul, Huma; Usman, Muhammad (Khyber Journal of Medical Sciences, 2021)
Introduction: There are no consistent data regarding the relationship between ABO / Rh-D blood types and susceptibility to SARS-CoV-2 infection from different regions. Objective: To determine the association between ABO/Rh-D blood types and susceptibility to SARS-CoV-2 infection among health care workers (HCW). Results: Out of 936 HCWs, 299 tested positive for SARS-CoV-2 antibodies. The proportion of blood type A, B, O and AB were 28.7%, 31.1%, 28.7% and 11.5%, respectively in those HCW who were positive for SARS-CoV-2 antibodies. 25.0 % HCWs with blood type O were positive for SARS-CoV-2 antibodies as compared to 34.4% with blood groups other than O and the difference was statistically significant. The odds of blood type-O for testing positive was 0.63 (95% CI 0.46 – 0.88, p=0.007). 34.4% HCW with blood type-A tested positive as compared to 30.9% with blood type other than A (OR 1.17, 95% CI 0.87 – 1.58, p=0.292). 35.3% HCW with blood type B were positive as compared to 31.9% with Non-B blood types (OR 1.25, 95% CI 0.94 – 1.68, p=0.126). There was no significant difference (p=0.968) between HCWs with blood type-AB and blood types other than AB to test positive (31.8 % and 32.0%, respectively, OR 0.99, 95% CI 0.64 – 1.53). 32.7 % HCWs with Rh-Positive blood types tested positive as compared to 20.7% with Rh-negative status (OR 1.86, 95% CI 0.97 – 3.57, p=0.058).